The Influence of the Whistleblowing System, Internal Audit, and Organizational Culture on the Prevention of Financial Fraud - Juwita Kusuma Putri S,; Arry Eksandy, (International Economic Conference of Business and Accounting, 2024)
This research aims to analyze the influence of the whistleblowing system, internal audit, and organizational culture on efforts to prevent financial fraud in the banking environment in the DKI Jakarta area. The research method used is quantitative with sampling using an accidental sampling questionnaire. The population studied was banking employees in the DKI Jakarta area. The data analysis technique used is hypothesis testing with multiple linear regression. The research results show that the whistleblowing system has a positive and significant influence on preventing fraud in DKI Jakarta banking. Internal audit also has a significant influence on fraud prevention. Likewise with organizational culture, which also has a positive and significant effect on preventing financial fraud. Thus, the findings of this research indicate that the implementation of a whistleblowing system, internal audit, and the formation of a strong organizational culture are important factors in efforts to prevent fraud in the banking sector.